Three-dimensional ADCIRC + SWAN storm surge modeling with coastal inundation in the Philippine archipelago - Gutierrez, Gwenevere Kay T.; Talibong, Ace Irish D.
The Philippines typically experiences more than twenty storms annually due to its location in the Pacific Ring of Fire and the South Asian Monsoon. On the 8th of November 2013, the country suffered from immense casualties caused by Typhoon Haiyan which produced storm surges with reported heights of up to 5 meters near Tacloban City. The country faces stronger storms yearly, thus, this research paper aims to develop an efficient model that produces real-time storm surge simulations with coastal inundation along the Philippine archipelago. The model used for this research is the Advanced Circulation (ADCIRC) model coupled with Simulating Waves Nearshore (SWAN) model. The ADCIRC model employs a barotropic three-dimensional run which incorporates a continuous-Galerkin finite element solution of the Generalized Wave Continuity Equation while the SWAN model incorporates an analog of the Gauss-Seidel sweeping method. An enhanced finite element mesh was also generated as imput using a combination of open-source digital elevation map processing software. SRTM30 Plus was used as bathymetric and topographic data with 926 meters of accuracy. Simulations showed a three-meter surge inundation along the Tacloban downtown and up to 1-meter surges along Tacloban airport which is comparable to the forecast heights by NOAH. A real-time storm surge simulation could reduce disaster risk, prepare residents of affected areas at the earliest possible time, and help them make informed decisions as to evacuations and safety measures.